DETERMINANTS OF FIRM VALUE WITH CAPITAL STRUCTURE AS AN INTERVENING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Wina Endra Nitha; Tri Widyastuti; Darmansyah, Darmansyah (Bajang Institute, 2025)
The main objective of this study is to evaluate and analyze the determinants of firm value, as well as to examine the mediating role of capital structure in the relationship between business risk, growth opportunities, and institutional ownership on firm value. The study focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period from 2019 to 2023. The research sample comprises 104 companies selected purposively based on specific criteria relevant to the objectives of the study. To analyze both the direct and indirect relationships among the examined variables, the study employs path analysis as the analytical method. The findings of the study indicate that business risk has a negative effect on firm value. Conversely, growth opportunities and institutional ownership are found to have a positive impact on firm value. In addition, capital structure exhibits a significant positive effect on firm value. A key contribution of this study is the identification of capital structure as a significant mediating variable that strengthens the influence of business risk, growth opportunities, and institutional ownership on firm value. This study reveals that capital structure plays a dominant mediating role in the relationship between business risk, growth opportunities, and institutional ownership and firm value. The integrative model proposed in this research offers a novel perspective by positioning capital structure as a strategic mechanism for value creation. These findings contribute to the theoretical understanding of firm value determination, particularly within the context of emerging markets during the post-crisis period of 2019–2023.